(untitled) (Research, Society and Development, 2023)
The knee is one of the joints most subject to ligament injuries and most susceptible to rotational forces. It has several ligaments that perform the primary function of balancing this joint in response to external forces and the anterior cruciate ligament is the longest and least resistant. In the postoperative period of this ligament, the physiotherapist must organize the procedure to prevent contractures and deformities, maintain tissue integrity, prevent the adverse effects of immobilization, minimize the patient’s pain, improve range of motion and muscle strength, using various care methods such as kinesiotherapy, electrotherapy, cryotherapy, among others. This article aims to present the contributions of physiotherapy to promoting quality of life for patients who have undergone this surgical procedure. In the methodology, the search for studies was carried out in electronic databases: LILACS, SciELO, Google Scholar, journals that publish articles in the health area, especially in postoperative physiotherapy. The inclusion criteria were: articles published between 2016 and 2023, with thematic relevance. 40 publications were identified, after applying the inclusion criteria, 32 studies remained. Regarding the recovery of a patient with an ACL injury, the physiotherapist must ensure that his patient is able to return to his activities, without risk of injury recurrence. It is concluded that physiotherapy plays a fundamental role in the post-operative recovery of the anterior cruciate ligament through its most diverse techniques.